Competition of gelatins in the refining of red wines - Fenocchio, Paolo (Pesquisa Agropecuaria Brasileira, 2014)
Four gelatins, two made in Brazil and two from Italy, were compared in the refining of five red wines of the Experimental Station of Bento Gonçalves in the amounts of 10, 20 and 30 g/hl. A reduction of colour intensity varying between 0.9 and 30.7 per cent, a reduction of the polyphenol content varying between 1.3 and 24.0 per cent and an increase in the wine softness index of between 0.4 and 10.9 per cent were observed in the treated wine compared to the controls. All these differences are dependent on the variety of the wine, its age, and the type and amount of gelatin used.